Smart functionalized phosphonic acid based copolymers: new structures for old purposes. Issue 18 (24th April 2020) - Solimando, Xavier; Catel, Yohann; Moszner, Norbert; Robin, Jean-Jacques; Monge, Sophie
Abstract : Innovative well-defined acidic photopolymerizable phosphorus-based copolymers were prepared and tested in well-known dental applications to improve the adhesion of dental self-etch adhesives (SEAs). Abstract : Innovative well-defined acidic photopolymerizable phosphorus-based copolymers were prepared and tested in well-known dental applications to improve the adhesion of dental self-etch adhesives (SEAs). Thus, innovative diblock copolymers of dimethyl-(methacryloyloxy)ethyl phosphonate (DMAOyEP) and 2-hydroxyethyl methacrylate (HEMA) were first synthesized by RAFT polymerization using a dithioester chain transfer agent (CTA) and then modified. First blocks were prepared with good control over the molecular weights and low dispersities. They were then used as macro-chain transfer agents (macroCTAs) to control well the polymerization of a second block. Appropriate functionalization of the diblock copolymers was performed. First, the dithiobenzoate chain-end was removed, leading to the discoloration of the copolymers. Secondly, polymerizable groups were incorporated by a partial functionalization of the hydroxyl group of the HEMA moiety with 2-isocyanatoethyl methacrylate (IEMA). Finally, the acidic copolymers were obtained via the deprotection of phosphonated ester groups. Following this strategy, a range of copolymers was developed and compared, varying the percentage of polymerizable groups, block compositions, molecular weights and architecture. Even if the adhesion of dental self-etch adhesives (SEAs) is currently adequate, improvements are still welcomed, and these new phosphonic acid-based materials are an opportunity to develop new dental formulations. So, dental adhesive properties were evaluated with shear bond strength (SBS) experiments to highlight the best developed materials. This contribution shows the interest of employing appropriate polymerization techniques, and appropriate functionalization reactions to develop new materials that could improve the specific properties of dental formulations.